Quantification and Costing of Domestic Electricity Generation for Armidale, New South Wales, Australia Utilising Micro Wind Turbines - Maklad, Yasser (International Journal of Energy Economics and Policy, 2014)
In this study, a general overview of energy and renewable energy sources available in Australia was introduced, household’s electricity situation in Australia was presented, and focus wind energy was conducted. A theoretical methodology for quantification and costing of selected micro wind turbines was introduced. This methodology was applied to Armidale city, New South Wales (NSW), Australia as a case study. The methodology involved utilisation of spread sheet application and HOMER software. Such methodology dealt with hourly household electric load in Armidale and hourly wind speed in Armidale as inputs and provided hourly power outputs from selected micro wind turbine as an output. As well, a sample of payback period calculations for the said selected wind turbines is calculated versus various wind speeds. This methodology can be applied to any other cities or towns. Undoubtedly, the ability of quantifying micro electricity generation resultant from micro wind turbines for a specific city or town and evaluating the share of households’ electric consumption at that city or town associated with the relevant payback periods opens the gate for further studies of feasibility and visibility of micro wind turbines. Keywords: Renewable energy in Australia; micro wind turbines; micro electricity generation; Household electricity consumption; Armidale city. JEL Classifications: C1; C2; C3; C6; C9 <!–[endif] –>